Influence of commercial dietary oils on lipid composition and testosterone production in interstitial cells isolated from rat testis - Hurtado de Catalfo, Graciela E. (2009)
The aim of this study was to examine the influence of dietary fat on lipid composition, as well as on the steroidogenic function of interstitial cells isolated from Wistar rats that had been fed semi-synthetic diets containing four different commercial oils (S soybean, O olive, C coconut, and G grape seed). Steroidogenic enzyme activities, lipid composition, and androgen production were measured in testicular interstitial cells. Lipid analysis included measurement of the contents of major lipid subclasses (neutral lipids, polar lipids, free and esterified cholesterol), as well as principal polar and neutral lipid fatty acyl compositions. Significant differences in lipid composition were observed among the groups, most of them reflecting the specific fatty acyl composition of the diet tested. Testosterone concentration was higher in O and C groups compared with S or G. In agreement with this observation, the activity of both key enzymes involved in testosterone biosynthesis (3-β-HSD and 17-β-HSD) was higher in O and C groups with significant differences between them (O > C). A significant negative correlation was found between cellular testosterone production and cellular cholesterol ester content. Additionally, testosterone concentration directly correlated with cholesterol levels. We conclude that dietary oils qualitatively and quantitatively modified the lipid composition of interstitial cells, producing either a direct or indirect regulatory effect on testicular steroidogenic function.